1989
DOI: 10.1083/jcb.109.6.3039
|View full text |Cite
|
Sign up to set email alerts
|

The identification of a novel synaptosomal-associated protein, SNAP-25, differentially expressed by neuronal subpopulations.

Abstract: Abstract. cDNA clones of a neuronal-specific mRNA encoding a novel 25-kD synaptosomal protein, SNAP-25, that is widely, but differentially expressed by diverse neuronal subpopulations of the mammalian nervous system have been isolated and characterized. The sequence of the SNAP-25 cDNA revealed a single open reading frame that encodes a primary translation product of 206 amino acids. Antisera elicited against a 12-amino acid peptide, corresponding to the carboxyterminal residues of the predicted polypeptide se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
478
0
8

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 762 publications
(516 citation statements)
references
References 50 publications
18
478
0
8
Order By: Relevance
“…[8][9][10][11][12][13][14][15] The synaptosomalassociated protein of 25 kDa (SNAP-25) gene lies in an area of previous suggestive linkage to intelligence (20p12-p11.2), 3 and is highly expressed by neurons in the hippocampus. [16][17][18] The SNAP-25 gene product is a presynaptic plasma membrane protein that is an integral component of the vesicle docking and fusion machinery that regulates neurotransmitter release. 17,19,20 It is also implicated in axonal growth and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10][11][12][13][14][15] The synaptosomalassociated protein of 25 kDa (SNAP-25) gene lies in an area of previous suggestive linkage to intelligence (20p12-p11.2), 3 and is highly expressed by neurons in the hippocampus. [16][17][18] The SNAP-25 gene product is a presynaptic plasma membrane protein that is an integral component of the vesicle docking and fusion machinery that regulates neurotransmitter release. 17,19,20 It is also implicated in axonal growth and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The SNAP-25 gene product is a presynaptic plasma membrane protein that is an integral component of the vesicle docking and fusion machinery that regulates neurotransmitter release. 17,19,20 It is also implicated in axonal growth and synaptic plasticity. 21 Three lines of evidence suggest a major role of SNAP-25 in learning and memory in humans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NSF is an ATPase and contains two homologous nucleotide-binding regions [3,4], and SNAPs mediate the association of NSF with membranes [5,6]. S611ner et al [7] identified VAMP-2 [8,9], syntaxin 1 [10][11][12], and SNAP-25 [13] as SNAP receptors (SNAREs). NSF, SNAPs and SNAREs are associated to form a 20S complex in membranes, and this complex is disassembled by Mg2+-ATP, whereby NSF is released from the membranes [7,14,15].…”
Section: Introductionmentioning
confidence: 99%